2021
DOI: 10.3390/su13105567
|View full text |Cite
|
Sign up to set email alerts
|

Busyness, Tenure, Meeting Frequency of the CEOs, and Corporate Social Responsibility Disclosure

Abstract: This study aimed to analyze the relationship between busyness, tenure, and the frequency of CEO meetings and corporate social responsibility (CSR) disclosure. This study used 624 observations from 78 companies listed on the Indonesia Stock Exchange and the Global Reporting Initiative (GRI) database for the 2010–2018 period. This study indicated that companies with busy CEOs or CEOs with long tenure produce fewer CSR disclosures. On the other hand, companies with CEOs who frequently attend board meetings genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 75 publications
(120 reference statements)
1
41
0
1
Order By: Relevance
“…The comprehensive option has 147 items. Following the methodology set out in [55], we also assume the firm will use the GRI guideline applied during the observation year if the firm does not state the series of GRI guidelines used.…”
Section: Variables Operationalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The comprehensive option has 147 items. Following the methodology set out in [55], we also assume the firm will use the GRI guideline applied during the observation year if the firm does not state the series of GRI guidelines used.…”
Section: Variables Operationalizationmentioning
confidence: 99%
“…Our control variables consist of profitability (ROA), leverage (LEV), firm size (FSIZE), firm age (LNAGE), board size (BSIZE), independent commissioner (INDCOM), and public accounting firm size (BIG4). These control variables will be defined in Appendix A and have been used based on prior studies [55,59].…”
Section: Variables Operationalizationmentioning
confidence: 99%
“…The main variables used in this study are the pessimistic tone in the income statements in MD&A, busy CEO, and CSR disclosure. CSR disclosure is the dependent variable measured using a CSR disclosure score obtained from the number of items disclosed in the sustainability report divided by the number of items that firms should disclose according to the GRI Index used [54]. This study used two versions of GRI as follows: the GRI G4.0 index, which is valid for 2013-2018 firm-year sustainability reporting, and GRI Standard, which is valid from 2018 firm-year sustainability reporting.…”
Section: Variable Definition and Data Sourcesmentioning
confidence: 99%
“…Then, referring to previous research [54,[57][58][59], several variables are used in this study. They include the number of firm boards (BOARD), the number of independent commissioners (INDCOM), number of audit committees (AUDCOM), firm size (FSIZE), firm age (FAGE), firm leverage (LEV), operational cash flow (OCF), firm losses (LOSS), and firm performance (ROE).…”
Section: Variable Definition and Data Sourcesmentioning
confidence: 99%
“…Unlike companies that have adopted sustainability initiatives based on compliance with current legislation, a number of companies have voluntarily introduced practices to increase their social, environmental, and economic performance beyond what is legally required [25]. The results of the study by Ratri et al [26] have shown that companies with CEOs who frequently attend board meetings engage in much more CSR disclosure. The results of the research of Ordóñez et al [27] indicate that the most indebted and largest companies disclose less information about the environment, in contrast to companies that are classified as having high solvency.…”
Section: Introductionmentioning
confidence: 99%